Investigation of Ground State Properties of Neutron-Rich Titanium Isotopes by the Use of SHF+BCS Method - Muhammad Zamrun; Ida Usman; La Aba (Jurnal Matematika & Sains, 2011)
The ground state properties of Ti-isotopes (44,46,48,50,52,56,58Ti) such as binding energy, density distribution, kinetic energy density distribution and local potential for proton and neutron are investigated using the Skyrme-Hartree-Fock (SHF)+Bardeen-Cooper-Schrieffer (BCS) method. In performing the SHF+BCS calculations, we use three most successfully Skyrme force parameters that are SIII, SkM*, and Sly4. It is found that the binding energy obtained with these three parameters is in well agreement with the experimental data. The calculated density distributions, kinetic energy densities and local potentials for proton and neutron using the three parameters for each titanium isotope are similar to each other, especially the slope and in the surface region. Our study indicates that SHF method is adequate to describe the ground state properties of the nucleus. Keywords: Skyrme-Hartree-Fock, Binding energy, Density distribution, Local potential. Investigasi Sifat-sifat Keadaan Dasar dari Isotop Titanium yang Berlebih Neutron dengan Metode SHF+BCS Abstrak Sifat-sifat keadaan dasar dari isotop-isotop Titanium (44,46,48,50,52,54,56,58Ti) berupa energi ikat, distribusi densitas, distribusi densitas energi kinetik serta potensial lokal untuk proton dan netron ditelaah dengan menggunakan metode Skyrme-Hartree-Fock (SHF)+Bardeen-Cooper-Schrieffer (BCS). Dalam melakukan perhitungan dengan metode SHF+BCS ini digunakan tiga set paramater untuk gaya-gaya Skyrme yaitu parameter SIII, SkM* dan Sly4. Energi ikat yang diperoleh dengan tiga set parameter ini sesuai dengan hasil eksperimen untuk semua isotop Titanium. Distribusi densitas, densitas energi kinetik dan potensial lokal yang diperoleh dengan tiga parameter tersebut untuk setiap isotop titanium Â mirip satu sama lain terutama untuk kemiringan dan daerah permukaan. Telaah ini menunjukkan bahwa metode SHF dapat digunakan untuk menentukan sifat-sifat keadaan dasar inti atom. Kata kunci: Skyrme-Hartree-Fock, Energi ikat, Distribusi densitas, Potensial lokal.